The Island of Theology and Religious Studies in the Global Age: Remarks on the Discipline and Its Prejudices - Tofighi, Fatima (Svensk teologisk kvartalskrift, 2026)
Theology and Religious Studies is still fraught with biases that in different ways underline the (religious) other. I try to uncover some of these biases, by calling attention to the infrastructures that do not allow certain people, questions, or themes to feel at home in the discipline. This is a call to provincialize theology and religious studies in Europe and North America.